Solid-state NMR and computational studies of 4-methyl-2-nitroacetanilide. - Harris, R; Ghi, P; Hammond, R; Ma, C; Roberts, K; Yates, JR; Pickard, C (2006)
Studies on the solid-state structure of two polymorphs of 4-methyl-2-nitroacetanilide (MNA) were conducted using magic-angle spinning (13)C, (15)N and (1)H NMR spectroscopy, together with first-principles computations of NMR shielding (including use of a program that takes explicit account of the translational symmetry inherent in crystalline structures). The effects on (13)C chemical shifts of side-chain rotations have been explored. Information derived from these studies was then incorporated within a systematic space-search methodology for elucidation of trial crystallographic structures from powder XRD.